2013
DOI: 10.1136/bmjopen-2012-002262
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis of HDR brachytherapy versus reoperation versus temozolomide alone: a retrospective cohort analysis of recurrent glioblastoma multiforme

Abstract: ObjectivesTumour recurrence of glioblastoma multiforme (GBM) after initial treatment with surgical resection, radiotherapy and chemotherapy is an inevitable phenomenon. This retrospective cohort study compared the efficacy of interstitial high dose rate brachytherapy (HDR-BRT), re-resection and sole dose dense temozolomide chemotherapy (ddTMZ) in the treatment of recurrent glioblastoma after initial surgery and radiochemotherapy.DesignRetropective cohort study.SettingPrimary level of care with two participatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…Based on the results of our retrospective study on recurrent glioblastoma, we now combine resurgery and HDR brachytherapy with intensive temozolomide chemotherapy. 2 We used the 1 week on/1 week off temozolomide with a daily dose of 150 mg/m 2 , until documented disease progression or unacceptable toxicity. We chose this more rigorous dose regimen of TMZ according to the publications of Wick et al who reported a 3 months PFS as high as 48% with an overall survival for 12 months of 81%.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the results of our retrospective study on recurrent glioblastoma, we now combine resurgery and HDR brachytherapy with intensive temozolomide chemotherapy. 2 We used the 1 week on/1 week off temozolomide with a daily dose of 150 mg/m 2 , until documented disease progression or unacceptable toxicity. We chose this more rigorous dose regimen of TMZ according to the publications of Wick et al who reported a 3 months PFS as high as 48% with an overall survival for 12 months of 81%.…”
Section: Methodsmentioning
confidence: 99%
“…However, a randomized controlled trial might be difficult to conduct given the obvious symptomatic benefits that surgery can provide in many instances and the survival benefits that HDR-BRT has showed in our recent retrospective studies. 2,12 This report compares and contrasts the outcomes and toxicity rates of a multimodal salvage therapy case group to a control group of patients treated with ddTMZ alone. Our CTCAE-based toxicity profile is quite favourably compared to the prior reports and is devoid of any high-grade toxicity, including radiation necrosis, hydrocephalus, intracranial hemorrhage, or meningitis.…”
Section: Combined Treatmentsmentioning
confidence: 97%
See 2 more Smart Citations
“…2 Options include repeat surgery, 39 chemotherapy (eg, temozolomide, 1018 irinotecan, 19 or nitrosoureas 20 ), bevacizumab, 21,22 experimental agents, or re-irradiation. 23 Numerous re-irradiation strategies exist, including conventional fractionated external beam radiotherapy (EBRT), 24,25 fractionated stereotactic radiotherapy, 23,26 hypo-fractionated stereotactic radiotherapy, 27 high dose rate (HDR) brachytherapy, 2830 low dose rate (LDR) brachytherapy, 3133 or single fraction SRS. Despite numerous options, median survival post-recurrence remains poor at 9–20 months.…”
mentioning
confidence: 99%